Exploring Opportunities for Mainstreaming HIV/AIDS in the Secondary-school Curriculum as an ESD Strategy - Raviro Chineka; Cecilia. K. Mukundu; Moliana Nyamukunda (Environmental Association of Southern Africa, 2013)
Education for sustainable development (ESD) embraces a variety of social- and environmental-health concerns, including the impact and implications of HIV/AIDS in respect of schooling and the quality of life of children and their communities. In this study, the researchers adopted a qualitative case study approach in which a school (Parirewa High School and its community in Domboshava) within a growth-point community in Zimbabwe was purposively selected because of its uniqueness as an information-rich source for HIV/AIDS and ESD interactions. The objective was to work with teachers in order to develop their capabilities and agency, thereby animating them to effectively integrate HIV/AIDS education in the formal school curriculum in a bid to reduce the negative impacts of HIV/AIDS on the quality of education and quality of life of vulnerable youths. Data was collected from 50 teachers by way of interactive workshops, focus-group discussions, document analysis, face-to-face interviews, observations and open-ended questionnaires. The findings suggest that, although teachers may be willing to embrace vulnerable learners in their teaching and change the way they teach and relate to their learners, there are a number of constraints. These include stigmatisation of those who teach the subject, a lack of knowledge and skills on how to deal with the sensitivity and the special needs created by HIV/AIDS, attitudes of society to the infected and the affected, and lack of support structures within the school. However, after participating in capacity building activities, teachers realised that the issue of HIV/AIDS can be integrated into any subject if teachers are taught how to mainstream, are prepared to change the way they perceive their roles, their subjects and their learners, and are committed to making a difference in the lives of the learners they teach. Teacher education thus needs reorientation in order to embrace skills necessary for teaching in contexts of risk, vulnerability and uncertainty. Further, it needs to embrace life skills education and ESD techniques for creating child-friendly schools and for bringing about healthy environments for both physical and psychosocial support within the school system. The study recommends that school administrators embrace HIV/AIDS and life skills education in the way schools are run and managed. In addition, relevant authorities should design legislation on mainstreaming HIV/AIDS so that the teaching of HIV/AIDS takes a whole-school approach. The conception of quality education and teacher competency need not be narrowly defined by learner pass rates alone, but may incorporate creativity and innovativeness and contribute to the creation of a better world.